Consumption of a 5-mg melatonin supplement does not affect 32.2-km cycling time trial performance - Brandenberger, K. J.; Ingalls, C. P.; Rupp, J. C.; Doyle, J. A. (The Journal of Strength and Conditioning Research, 2018)
Some studies suggest that exogenous melatonin supplementation may improve athletic performance in hot humid environments because of its precooling effect. However, melatonin is also consumed as a sleep aid for its depressive effects on the central nervous system (CNS), which may hinder performance. Therefore, this study was conducted to determine whether consuming a 5-mg supplement of melatonin would affect performance in a laboratory-simulated 32.2-km cycling time trial. The time trial was conducted in a thermoneutral environment to separate CNS depressive effects of the melatonin from the cooling effects. Trained male subjects (n = 10; VO2max = 62.7 ± 6.3 ml/kg/min; age = 25.1 ± 4.0 years; mass = 69.9 ± 9.1 kg; height = 176.0 ± 7.1 cm) performed three 32.2-km time trials on an electronically braked cycle ergometer. The first trial was a familiarization. During the 2 experimental trials, subjects received in a random order either a placebo or a 5-mg melatonin supplement 15 minutes before exercise in a double-blind, crossover design. Variables were measured before exercise and at 8-km intervals. The mean 32.2-km time trial completion times for the melatonin (64.94 ± 5.95 minutes) and placebo (65.26 ± 6.85 minutes) trials were not different (p = 0.682). The mean time trial power output for the melatonin (190.4 ± 40.4 watts) and placebo (190.0 ± 45.7 watts) trials was not different (p = 0.927). Rectal temperature was not significantly different for melatonin compared with placebo (p = 0.827). These results suggest that a 5-mg melatonin supplement administered 15 minutes before exercise does not measurably impact the performance of a 32.2-km cycling time trial in a thermoneutral environment.